Structural basis for major histocompatibility complex (MHC)-linked susceptibility to autoimmunity: charged residues of a single MHC binding pocket confer selective presentation of self-peptides in pemphigus vulgaris. - Wucherpfennig, K W (1995)
Human T-cell-mediated autoimmune diseases are genetically linked to particular alleles of MHC class II genes. Susceptibility to pemphigus vulgaris (PV), an autoimmune disease of the skin, is linked to a rare subtype of HLA-DR4 (DRB1*0402, 1 of 22 known DR4 subtypes). The PV-linked DR4 subtype differs from a rheumatoid arthritis-associated DR4 subtype (DRB1*0404) only at three residues (DR beta 67, 70, and 71). The disease is caused by autoantibodies against desmoglein 3 (DG), and T cells are thought to trigger the autoantibody production against this keratinocyte adhesion molecule. Based on the DRB1*0402 binding motif, seven candidate peptides of the DG autoantigen were identified. T cells from four PV patients with active disease responded to one of these DG peptides (residues 190-204); two patients also responded to DG-(206-220). T-cell clones specific for DG-(190-204) secreted high levels of interleukins 4 and 10, indicating that they may be important in triggering the production of DG-specific autoantibodies. The DG-(190-204) peptide was presented by the disease-linked DRB1*0402 molecule but not by other DR4 subtypes. Site-directed mutagenesis of DRB1*0402 demonstrated that selective presentation of DG-(190-204), which carries a positive charge at the P4 position, was due to the negatively charged residues of the P4 pocket (DR beta 70 and 71). DR beta 71 has a negative charge in DRB1*0402 but a positive charge in other DR4 subtypes, including the DR4 subtypes linked to rheumatoid arthritis. The charge of the P4 pocket in the DR4 peptide binding site therefore appears to be a critical determinant of MHC-linked susceptibility to PV and rheumatoid arthritis.